Canva-Based Learning Media And Its Impact on Students’ Achievement in the Digestive System Topic - Prassita Sari, Yuneva Dwi; Degeng, I Nyoman Sudana; Sitompul, Nurmida Catherine (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
his study aims to examine the influence of Canva-based instructional media and learning motivation on the learning outcomes of fifth-grade elementary students in the topic of the human digestive system within the IPAS subject. The research adopts a quantitative approach using a quasi-experimental method with a 2x2 factorial design and an ex post facto technique. The population consisted of fifth-grade students from SDN Kabuh. Data were collected through tests of learning outcomes and motivation questionnaires. The analysis showed that the use of Canva-based media had a significant effect on student achievement. Furthermore, learning motivation independently contributed to improved learning outcomes. The interaction between the two variables was also significant, indicating that high motivation strengthened the positive effect of Canva-based media. This research confirms the importance of integrating visual-digital tools with internal student factors to enhance science learning in elementary education